2022
DOI: 10.1016/j.ijid.2022.01.064
|View full text |Cite
|
Sign up to set email alerts
|

Serological reactivity of inactivated SARS-CoV-2 vaccine based on an S-RBD neutralizing antibody assay

Abstract: Objectives This study aimed to explore the regularity of S-RBD domain antibody reactivity after immunization with inactivated SARS-CoV-2 vaccine and evaluate the immune response effect of this vaccine. Design or methods Venous blood samples were collected from 1156 healthcare workers who participated in the phase III clinical trial of SARS-CoV-2 inactivated vaccine. The S-RBD domain antibody levels in serum were detected by ELISA 14 days after the first and second activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…After title and abstract screening, we retrieved 193 full‐text reports for further review. Finally, 11 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 articles met our inclusion criteria. All included studies were of high quality (NOS > 6).…”
Section: Resultsmentioning
confidence: 99%
“…After title and abstract screening, we retrieved 193 full‐text reports for further review. Finally, 11 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 articles met our inclusion criteria. All included studies were of high quality (NOS > 6).…”
Section: Resultsmentioning
confidence: 99%
“…The study reported that the S-RBD-neutralizing antibody was significantly lower in the BMI >25.00 kg/m 2 group compared to the 21.00–25.00 kg/m 2 group ( p <0.05). Additionally, the S-RBD-neutralizing antibody in both the 21.00–25.00 kg/m 2 and >25.00 kg/m 2 groups was significantly lower than that of the ≤21.00 kg/m 2 group ( p <0.05) [ 36 ]. In our study, the healthcare workers had a median body weight of 65.25 (55–73.5) kg and a median BMI of 23.61 (21.51, 26.24) kg/m 2 , which is considered overweight in the Asian population.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of the colour was measured at 450 nm using a MultiSkan FC reader (51119000, Thermo Fisher Scientific Inc., Waltham, MA, USA). The anti-SARS-Cov-2 RBD neutralizing antibody were detected using SARS-CoV-2 Neutralizing Antibodies Test Kit (DD3101, Vazyme Biotech, Nanjing China) according to the manufacturer’s protocol as previously reported [ 24 ], which is based on the competition between the neutralizing antibodies in serum and ACE2 to horseradish peroxidase-labelled RBD protein. The optical density (OD) was measured at 450 nm using a MultiSkan FC reader.…”
Section: Methodsmentioning
confidence: 99%
“…The optical density (OD) was measured at 450 nm using a MultiSkan FC reader. The signal inhibition rate (SIR) was calculated with the equation SIR = (1-OD of sample/mean OD of negative control) × 100% [ 24 ]. The serum levels of IFN-γ, IFN-α, interleukin (IL)−1β, IL-2, IL-4, IL-5, IL-6, IL-10, IL-17A and tumour necrosis factor (TNF)-α were measured using an Aimplex kit (P010041, CEGER, Hangzhou, China) and flow cytometry (BD FortessaX20), following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%